Trends in IPOs: The Evidence from CEE Capital Markets - Tomas Meluzin; Marek Zinecker (Institute of Economic Research (IER), 2015)
The purpose of this paper is to investigate IPO developments across five CEE countries between 2003 and 2012. Using a wider range of methods and different data sets we intend to complement the previous research. Applying descriptive statistics, relevant local developments are analysed first before being compared with leading European markets (London Stock Exchange and Deutsche Börse). We also investigated the assumption that a growing market has an explanatory power for the accelerating IPO activity. For this purpose we performed a Spearman correlation analysis. The data were evaluated at the significance level of ? = 5 %. All CEE capital markets recorded strong dynamism over the observed period. All fundamental capital market parameters increase the attractiveness of individual capital markets, although their values lag behind developed European capital countries. The unambiguous leader in the region is Poland with a flourishing IPO market. Our assumption that a growing market has a positive impact on IPO activities could not be supported by empirical evidence.
Keywords: E44; G23; G32; 330; IPO; Going Public; Trends; Financial Markets; CEE